(untitled) (Bulletin of criminological association of Ukraine, 2023)
The scientific article emphasizes that the problem of "traffic", and in particular its "safety", is by no means deprived of the attention of scientists and practitioners. However, it is worth evaluating the real state of the problem’s development based not on scientific, or even regulatory and legal achievements. After all, there are more objective indicators, namely: the number of traffic accidents that led to the death of people, injuries, material damage, etc. It has been proven that "traffic" is a phenomenon that is not only deeply integrated into the everyday life of every person, but also has broad objective connections with the economic state of the state in its various branches. This, without a doubt, justifies the large set and variety of normative legal acts that regulate individual issues of "traffic" and its "safety". A successful (quality) settlement of the issues of "traffic" and its "safety" requires finding a balance between a dynamic set of real safety risks, the latest technical and technological achievements and the significant advantages of expanding the space of officially permitted opportunities (for road users and for other persons, the content and the success of which depends on normalization of "traffic"). This feature determines the dynamism of the system of national regulatory and legal acts on the regulation of "traffic" issues, and also explains the involvement of a considerable number of subjects in the relevant measures for proper regulation at various levels of the issuance of regulatory and legal acts. Since the list of relevant entities, their separate rights and obligations are fixed in the Law of Ukraine "On Road Traffic" (which is already emphasized in the first articles of this Law), it is appropriate to consider this legislative act as a profile (main, special or sectoral) ) on defining issues of "administrative and legal regulation" of the specified problem. Attention is drawn to the fact that the intensity of the production of law-making initiatives and implemented innovations regarding the regulation of the peculiarities of the Law of Ukraine "On Road Traffic" remains quite high. This situation has been observed since the period when our state became aware of its European vector of development.